Humanitarian Diplomacy as a Tool of International Relations: the Position of the Kazakhstani Foreign Policy Elite and the Experience of Foreign Countries (International relations and international law Journal, 2022)
The article provides an analysis of the development of humanitarian diplomacy in terms of current and new challenges, such as pandemic, armed conflicts. The potential for conflict will always exist in relations between states. The role of diplomacy is to anticipate and resolve problems before they escalate into conflicts. When conflicts are inevitable, diplomats work to resolve differences peacefully to avoid violent clashes. The protection of human rights is a critical area of international conflict resolution, in which diplomats play a key role. Countries with more human rights violations are more prone to fast-spreading and violent conflict. Diplomats work to prevent human rights violations and promote respect for the political, civil, economic and social rights of people in countries around the world. In recent decades, human rights issues, once considered the internal affairs of individual states, have become the subject of humanitarian interventions, often led by the UN and the world’s superpowers. As a result, military intervention can be accompanied by humanitarian intervention, which is sometimes perceived as a violation of the sovereignty of the affected countries. It is in these conflict situations that diplomacy and human rights are directly linked. Humanitarian diplomacy tries to resolve potential problems through negotiations, while at the same time finding ways to help those affected by the crisis. Humanitarian diplomacy emphasizes the importance of stable political relationships to help and support vulnerable people or groups whose rights and interests are threatened and whose voices are silenced in the midst of more serious socio-political conflicts. The concept of human rights is more important now than at any time since the Cold War, as global forces shift and regional divisions flare up in response to the political, economic and social upheaval caused by the COVID-19 pandemic. Consideration of foreign experience in the humanitarian sphere can identify the role of humanitarian diplomacy in the implementation of the country’s foreign policy. The article examines the models of the humanitarian policy of France as the main vector of the foreign policy of the country, Russia and the United States in the context of humanitarian assistance to Syria, which have conflicting interests in relation to the Middle Eastern country. It also examines the experience of Kazakhstan in the field of humanitarian diplomacy, as well as the position of the foreign policy elite and prospects in this area.Key words: Humanitarian diplomacy, pandemic, Kazakhstan, foreign countries, international humanitarianlaw.